Teacher Research and Adult Learning in Music Education (LEARNing Landscapes, 2015)
The purpose of this study was to describe the experiences of seven music educators who designed and implemented teacher research in their classrooms in relation to the Merriam, Caffarella, and Baumgartner (2007) theory of adult learning. Findings are presented within participant profiles and suggest that motivations to participate included a desire to be a better teacher and an interest in collaborating with the University. The collaboration helped the participants to continue with their studies as did their curiosity about the learning of their students. The issue of time hindered some of the participants’ ability to complete their studies.
Keywords: teacher research; music education; adult learning